LANGUAGE DISORDER EXPERIENCED BY A MAN WITH ASD AS A LEADER OF CONSERVATION ORGANIZATION - Khairunnisya Lubis; Rahmadsyah Rangkuti (Universitas Bengkulu, 2022)
This paper aims to identify the different types of language disorders that a man with autism spectrum disorder (ASD), especially Asperger Syndrome (AS), can experience. The information was in the form of phonemes, words, phrases, clauses, and sentences that he used in his everyday utterances as the leader of a local conservation group. The objective of this research is to classify different types of pragmatic impairment in AS characters and to clarify the pragmatic impairment that AS individuals face in his everyday life which conclude unresponsive, unbalanced, mismatched, lack of control and lack of playfulness based on the research problems. Academically, this analysis is intended to make substantial contributions to the fields of psycholinguistics and pragmatics. It's relevant to the psycholinguistics perspective because it's about the disability. It is a practical guide that professionals, lecturers, students, physicians, language pathologists, therapists, and readers from a variety of fields can use.